The influence of diabetes mellitus on periodontal tissues: a pilot study - Um, Yoo-Jung (Korean Academy of Periodontology, 2010)
PURPOSE: The purpose of this study was to preliminarily evaluate the influence of diabetes mellitus (DM) on periodontal tissue without establishment of periodontitis. METHODS: Seven-week-old db/db mice were used for the diabetic experimental group and systematically healthy mice of the same age were used as controls. After 1 week of acclimatization, the animals were sacrificed for hard and soft tissue evaluation. The pattern of bone destruction was evaluated by stereomicroscope evaluation with alizarin red staining and radiographic evaluation by microscopic computerized tomography images. Histological evaluation was performed with hematoxylin and eosin stain for evaluation of soft tissue changes. RESULTS: In both stereomicroscope evaluation and radiograph image analysis, aggressive form of bone destruction was observed in diabetic animals when compared to the systematically healthy controls. In histological evaluation, apical migration of junctional epithelium with slight inflammatory cell infiltration was observed with disarrangement of connective tissue fibers. CONCLUSIONS: Within the limits of this study, diabetic animals presented distortion in periodontal attachment and an aggressive bone loss pattern when compared to the healthy controls, suggesting that DM has an independent effect on periodontal tissue destruction irrespective of the presence or absence of periodontal disease.